1998
DOI: 10.3171/jns.1998.89.5.0861
|View full text |Cite
|
Sign up to set email alerts
|

Waterjet dissection of the brain: experimental and first clinical results

Abstract: Control of bleeding during dissection is a problem that is still not completely resolved in neurosurgical procedures. To overcome this problem in some settings, the authors, in close collaboration with their institution, developed a new device for blunt dissection of brain tumors that is based on a waterjet technique. This report describes their first experimental and clinical experience with this new method. Numerous cutting experiments were performed in porcine cadaver brains. The best results were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 16 publications
2
20
0
3
Order By: Relevance
“…Histology revealed no degenerative or necrotic damage on the surface cut with this device. This result is very similar to those obtained with the other water-jet devices [14,17,19]; however, our device can eliminate the disadvantages associated with the former, such as obscuration of the operative field and the splashing of bloody fluid, thanks to its pulsed operation. Moreover, while it has been reported that the slight delay between switching on such devices and the projection of the fluid was of minor inconvenience [14], our device possesses an even smaller time delay because the jet-driving source ± that is, the tip of the optical fiber ± exists in the distal region of the nozzle.…”
Section: Discussionsupporting
confidence: 91%
“…Histology revealed no degenerative or necrotic damage on the surface cut with this device. This result is very similar to those obtained with the other water-jet devices [14,17,19]; however, our device can eliminate the disadvantages associated with the former, such as obscuration of the operative field and the splashing of bloody fluid, thanks to its pulsed operation. Moreover, while it has been reported that the slight delay between switching on such devices and the projection of the fluid was of minor inconvenience [14], our device possesses an even smaller time delay because the jet-driving source ± that is, the tip of the optical fiber ± exists in the distal region of the nozzle.…”
Section: Discussionsupporting
confidence: 91%
“…In 1982, waterjet was used in medical field. It can effectively dissect liver, kidney, and brain tissues [13]. Cesarani et al [14] invented a kind of high frequency pulse "waterjet"(hydrojet), conjuncted with application of fiber endoscope, could remove large stone, and also clean fragmented stone.…”
Section: Discussionmentioning
confidence: 99%
“…15 Jah ren ein ge setzt [1,17,20,34]. Die Hydro dis sek ti ons tech nik hat sich hier bei als blu tungs ar mes und ge we be s e lek ti ves Verfah ren vor al lem in der Ab do mi nal chir urgie, der Or tho pä die, der Op thal mo lo gie, der Neu ro chir ur gie und der Uro lo gie bewährt [3,4,9,19,36,37,49,51,52,53].…”
Section: Tonsill Ek To Mie In Hy Dro Dis Sek Ti Ons Tech Nikunclassified